2018
DOI: 10.2147/jpr.s169701
|View full text |Cite
|
Sign up to set email alerts
|

OnabotulinumtoxinA injections for atypical odontalgia: an open-label study on nine patients

Abstract: BackgroundAtypical odontalgia (AO) manifests as continuous pain in the region of one or several teeth, in the absence of signs of dental pathology. Currently, there is insufficient evidence to establish treatment guidelines for AO. The aim of this study was to describe the effectiveness and safety of treatment with OnabotulinumtoxinA (OnabotA) on a series of patients with AO.MethodsNine patients with AO (four males and five females, aged between 31 and 77 years) received injections of OnabotA in the region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(64 citation statements)
references
References 20 publications
4
51
0
Order By: Relevance
“…This short therapeutic window means that lidocaine injections are not routinely used. Localised botulinum toxin injections have been reported to produce significant reductions in pain and few side effects in patients suffering from PIDP. It must be noted that this therapy is new, so no RCTs or comparisons with placebos are currently available and papers on the topic comprise of case studies rather than trials with the largest study containing just 9 patients.…”
Section: Impactmentioning
confidence: 99%
“…This short therapeutic window means that lidocaine injections are not routinely used. Localised botulinum toxin injections have been reported to produce significant reductions in pain and few side effects in patients suffering from PIDP. It must be noted that this therapy is new, so no RCTs or comparisons with placebos are currently available and papers on the topic comprise of case studies rather than trials with the largest study containing just 9 patients.…”
Section: Impactmentioning
confidence: 99%
“…Currently, there is insufficient evidence to establish a treatment protocol for AO 25 . Tricyclic antidepressants, antiepileptics, anesthetics, and botulinum toxin, although reducing the pain of the patient 3,22,25 , have limited activity and have no proven effectiveness [25][26][27] . Generally, the dental surgeon is the first healthcare professional with whom the AO patient consults.…”
Section: Review Articlementioning
confidence: 99%
“…García-Sáez et al 25 The use of botulinum neurotoxin type A has been shown to reduce pain in patients with AO. However, randomized controlled trials (RCT) are suggested to prove their effectiveness.…”
Section: J the Characteristics Do Not Fall Into Any Other Diagnosticmentioning
confidence: 99%
See 2 more Smart Citations